Spaceman of Bohemia - Kalfař, Jaroslav 1988- (Little, Brown and Company, 2017)
"When Jakub Procha is sent into space to examine a cosmic dust cloud covering Venus, it may be a solo suicide mission. Dreaming of becoming a national hero and desperate to atone for his father's sins as a Communist informer, he leaves his beloved wife behind and launches into the galaxy. But things aboard spaceship JanHus1 quickly turn weird, and, to make matters worse, he soon learns that his wife has disappeared without a trace back on Earth. As his spaceship hurtles toward an unknown danger and his sanity wavers, Jakub encounters an unlikely fellow passenger ... a giant alien spider. He and his strange arachnid companion form an unlikely bond over late-night refrigerator encounters, where they talk philosophy, love, life, death, and the incomprehensible deliciousness of bacon. But when their mission is thrown into crisis by secret Russian rivals, Jakub is forced to make violent decisions ... recalling the tortured past and dark political heritage he's buried ... in a desperate quest to return to his Earthly life. Packed with nail-biting thrills, exuberant heart, and surprising and absurd humor in the lineage of Kafka and Vonnegut, Spaceman of Bohemia offers an extraordinary vision of the endless human capacity to persist ... and risk everything ... in the name of love and home"...